Investigating the Use of Calcined Quartzite Dust as a Partial Replacement of Cement in Concrete - Sharif Olupot (Uganda Christian University, 2024)
The majority of architecture and building worldwide is built with concrete, the most widely utilized man-made material worldwide. Since its creation in antiquity, concrete has been fashioned by stiff molds, which have greatly influenced its nature. To reduce the harmful effects that regular Portland cement (OPC) has on the environment, researchers have been working to create more sustainable cementitious systems in recent years. Several attempts have been made to create sustainable binders by replacing a large percentage of OPC with pozzolans, such as slag, fly ash (FA), palm oil fuel ash (POFA), metakaolin (MK), silica fume (SF), rice husk ash (RHA), etc. The purpose of this study was to ascertain how adding calcined quartzite dust (CQD) as a binder would affect the compressive and flexural properties of conventional concrete in a partial substitution of cement. The research was conducted in three phases. The physical and chemical characteristics of CQD were analysed. Then the performance of concrete incorporating the different percentage replacement of 10%, 15%, 20% 25% and 30% of cement with CQD was determined. The workability, water absorption, compressive strength and flexural strength was determined. Finally, the appropriate working mix design for the concrete was determined at 10% percentage replacement of cement with CQD and a mix design with the chosen optimal percentage replacement of cement with CQD was then determined. The findings of this research project concluded that CQD can be used as an effective partial replacement of cement at 10% percentage replacement of cement with CQD.